23 Hidden: a hospice inpatient deep vein thrombosis detection study to explore the prevalence, symptom burden and natural history of venous thromboembolism in people with advanced cancer. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Johnson, MJ; Noble, SIR; Swan, F; Allgar, V; Napier, E; Nelson, A; Watson, M; White, C
Abstract : Background: The deep venous thrombosis (DVT) prevalence in advanced cancer is unconfirmed and it is unknown whether current international thromboprophylaxis guidance is applicable to this group. We determined prevalence and predictors of femoral DVT in patients admitted to specialist palliative care units (SPCU). Methods: Prospective longitudinal observational study in five SPCUs in England, Wales and Northern Ireland. Consecutive adults with cancer underwent bilateral femoral vein ultrasonography on admission and weekly until death or discharger for a maximum of three weeks. Data were collected on performance status, attributable symptoms and variable known to be associated with venous thromboembolism. Patients were ineligible if admitted for terminal care (estimated prognosis <five days). Prevalence was estimated with 95% confidence intervals (CI). DVT predictors and survival were explored using regression analyses. Sensitivity analysis excluded early scans to account for a technical learning curve. Results: 343 participants (68·2 [SD 12·8] 25 to 102 years; men 52%; AKPS 49 [SD 16·6] 20% to 90%) were recruited. Of 273 evaluable scans, 92 (34%, CI 28% to 40%) showed DVT. Excluding early scans, 64/232 (28%, 22% to 34%) showed DVT. Four participants with a 'no DVT' scan on admission developed a DVT on repeat scanning over 21 days. Previous thromboembolism, bedbound ≤12 weeks for any reason (p=0.003) and lower limb oedema (p=0.009) independently predicted DVT. Serum albumin (p=0.430), thromboprophylaxis (p=0.173) and survival (p=0.473) were unrelated to DVT. Conclusions: These novel data show approximately one third of SPCU admissions with advanced cancer had a femoral DVT. DVT was not associated with thromboprophylaxis, survival or symptoms other than leg oedema. Findings are consistent with VTE being a manifestation of advanced disease rather than a cause of premature death. Thromboprophylaxis for SPCU in-patients with poor performance status seems of little benefit.